Gating Behavior of Endoplasmic Reticulum Potassium Channels of Rat Hepatocytes in Diabetes - Ghasemi, Maedeh (Pasteur Institute of Iran, 2014)
Background: Defects in endoplasmic reticulum homeostasis are common occurrences in different diseases, such as diabetes, in which the function of endoplasmic reticulum is disrupted. It is now well established that ion channels of endoplasmic reticulum membrane have a critical role in endoplasmic reticulum luminal homeostasis. Our previous studies showed the presence of an ATP-sensitive cationic channel in endoplasmic reticulum. Therefore, in this study, we examined and compared the activities of this channel in control and diabetic rats using single-channel recording techniques. Method: Male Wistar rats were made diabetic for 2 weeks with a single dose injection of streptozotocin (45 mg/kg). Ion channel incorporation of rough endoplasmic reticulum of diabetic hepatocytes into the bilayer lipid membrane allowed the characterization of K(+) channel. Results: Ion channel incorporation of rough endoplasmic reticulum vesicles into the bilayer lipid revealed that the channel current-voltage (I-V) relation with a mean slope conductance of 520 ± 19 pS was unaffected in diabetes. Interestingly, the channel Po-voltage relation was significantly lower in diabetic rats at voltages above +30 mV. Conclusion: We concluded that the endoplasmic reticulum cationic channel is involved in diabetes. Also, this finding could be considered as a goal for further therapeutic plans.